THE SETTLEMENT OF INDUSTRIAL RELATIONS DISPUTES: LEGAL ACTIONS FOR LABORERS IN DEFENDING THEIR RIGHTS - Ali, Muhammad (Jurnal Pembaharuan Hukum, 2024)
The aim of this research is to find out what potential legal actions can be taken by laborers in the settlement of their industrial relations disputes. The research method used a normative legal research design method or legal library research. The results and findings showed that legal efforts against laborers to protect their rights have several alternative solutions, the settlement of industrial relations disputes in Indonesia is characterized by a tiered approach that emphasizes resolution through dialogue and mutual understanding, before escalating to judicial intervention. The Bipartite process highlights the importance of direct negotiation between laborers and employers to maintain workplace harmony, while the Tripartite process involves government participation, aiming to foster broader cooperation and consensus among all stakeholders. Should these conciliatory efforts fail, parties are entitled to seek resolution through the courts, marking a transition to a more adversarial form of dispute resolution. Additionally, mediation serves as a critical preliminary step, mandated by Law Number 2 of 2004, to attempt reconciliation and find a mutually agreeable solution before resorting to litigation. Collectively, these mechanisms reflect a comprehensive and structured approach to managing industrial relations disputes, prioritizing peaceful resolution and the preservation of professional relationships, with the court system serving as a final recourse for unresolved conflicts. In the future of this research is to increase knowledge about the process of resolving industrial relations disputes involving laborers, as well as increasing the legal protection of laborers in industrial relations, especially those related to laborers' rights in termination of employment.